The lesser evil : moral approaches to genocide practices - Dubiel, Helmut, 1946-; Motzkin, Gabriel (Totalitarian movements and political religions., 2004)
This book comprises 14 essays by scholars who disagree about the methods and purposes of comparing Nazism and Communism.